Synovial osteolipoma - Radha Sistla; Josyula Venkata Satya; Tameem Afroz (Wolters Kluwer Medknow Publications, 2016)
Intraarticular synovial osteolipoma is an extremely rare tumor. Only two cases have been reported earlier to the best of our knowledge. It is a rare histological variant of lipoma, which contains mature lamellar bone. The largest tumor reported so far in the joint is 3 cm × 4 cm. Knee is a most common site. We report a large osteolipoma measuring 12 cm × 10 cm in the knee.